Comparative efficacy of r-hFSH Alfa + r-LH versus r-hFSH delta + hMG in poor ovarian responders - Baldini, Giorgio Maria; Baldini, Domenico; Lot, Dario; Malvasi, Antonio; Laganà, Antonio Simone; Palumbo, Mario; Damiani, Gianluca Raffaello; Trojano, Giuseppe (Frontiers in Endocrinology, 2025)
IntroductionPoor ovarian response (POR) remains a major limitation in assisted reproductive medicine. Direct comparisons between r-hFSH alfa + r-LH and r-hFSH delta + hMG in this population are scarce.MethodsThis retrospective study included 437 POR patients treated between 2018 and 2022. Controlled ovarian stimulation involved either r-hFSH alfa + r-LH (Group A) or r-hFSH delta + hMG (Group B). After exclusions, 148 patients per group who reached embryo transfer were analyzed. Primary outcomes were total oocytes, metaphase II (MII) oocytes and embryos. Secondary outcomes included β-hCG positivity, clinical pregnancy and pharmacoeconomic evaluation.ResultsGroup A showed significantly higher numbers of oocytes (p=0.01), MII oocytes (p=0.02) and embryos (p=0.03). No significant differences in biochemical or clinical pregnancy were observed (OR 1.12; 95% CI: 0.79–1.59). The r-hFSH alfa + r-LH protocol required lower total gonadotropin doses and resulted in an average saving of €690 per additional MII oocyte.DiscussionThe r-hFSH alfa + r-LH regimen improved ovarian response and cost-efficiency without affecting pregnancy outcomes. Prospective randomized trials are needed to confirm these results.